Landscape and Tourism, Landscapes of Tourism - Terkenli, Theano S. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Landscape is central to tourism. It is key to the development, marketing/promotion, and consumption of tourism destinations, to triggering and sustaining tourism markets, and to enticing tourist dreams, fantasies, and behaviors. From 'sight-seeing' practices-at the basis of all tourism activities-landscape figures prominently all the way to the overall spatial planning and management of a destination for tourism development. The intertwined relationship between tourism and landscape comes with a series of costs and benefits, in the context of tourism landscapes. Landscapes of tourism reflect and stage recreational trends, multifunctional livelihood systems, conflicts and opportunities for employment and income generation, as well as human, cultural, and natural resource management and use. This Special Issue aims to enhance the interdisciplinary scientific dialogue on these issues and challenges, while highlighting their range and significance for tourism and the landscape, in terms of theory, empirical practice, approach, policy, ethics, and future prospects. Some of the questions posed for consideration here are: What are landscapes of tourism, for whom and how/why? What is the role of the landscape in tourism promotion, attraction, and experience? How does tourism affect the landscape? What lessons do the history and geography of tourism have to offer to tourism landscape stewardship? How may we best plan for and manage the landscape in the context of various forms of tourism growth and spread, at various scales? Scholarly advances in the past few decades have steadily built on a diverse-but spread-out and not adequately connected-bibliographical basis for future research. Much remains to be understood and exchanged as landscape and tourism-two highly complex and multifaceted scientific areas-come together in the scope of this Special Issue in a variety of ways across time, space, and culture.